2016
DOI: 10.4137/sart.s39921
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Disorder and Co-occurring Substance Use Disorder – A Systematic Review

Abstract: OBJECTIVEPatients with co-occurring autism spectrum disorders (ASD) and substance use disorder (SUD) require special attention from clinical services. Screening for this co-occurrence is not generally an integral part of routine clinical assessments, and failure to identify and understand this group of patients may contribute to a worsening of their symptoms and/or an increase in drug abuse. Thus, there is a need to review the evidence base on patients with co-occurring ASD and SUD in order to enhance clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
58
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 34 publications
(45 reference statements)
1
58
0
1
Order By: Relevance
“…11,12 In fact, the results of a small number of studies suggest that autistic individuals may be at lower risk of substance use compared with their nonautistic counterparts. [11][12][13][14][15] However, these studies were largely conducted among patients seen in or referred to psychiatry clinics, or among individuals with psychiatric diagnoses seeking treatment, likely biasing samples toward autistic individuals with higher intensity of traits.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 In fact, the results of a small number of studies suggest that autistic individuals may be at lower risk of substance use compared with their nonautistic counterparts. [11][12][13][14][15] However, these studies were largely conducted among patients seen in or referred to psychiatry clinics, or among individuals with psychiatric diagnoses seeking treatment, likely biasing samples toward autistic individuals with higher intensity of traits.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with borderline personality disorder (BPD) elevated autistic traits were observed and these were related to clinical features like suicidality (Dell'Osso, Cremone, Carpita et al , ). Additionally, recent research indicates that substance use disorder (SUD) is an important, but so far sparsely studied, co‐occurring phenomenon in ASD (Arnevik & Helverschou, ; Rengit, McKowen, O'Brien, Howe & McDougle, ), and ASD and autistic traits are a risk factor for substance (mis‐)use and related problems (Alwis, Agrawal, Reiersen et al , ; Butwicka, Långström, Larsson et al , ; Mulligan, Reiersen & Todorov, ). SUD in turn is a common comorbidity of BPD (Trull, ), and co‐occurring these two severe psychiatric disorders indicate a challenge to successful treatment (Bornovalova & Daughters, ; McMain & Ellery, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on treatment outcomes in eating disorders showed that patients with concurrent ASD, elevated levels of ASD traits or ASD‐related developmental difficulties responded less successfully to treatment, compared to patients without concurrent ASD and low ASD traits, respectively (Nielsen et al ., ; Stewart, McEwen, Konstantellou, Eisler & Simic, ; Tchanturia, Larsson & Adamson, ). In SUD, conventional treatment methods might not be appropriate for patients with concurrent ASD, like for example group therapy because of deficits in social skills as well as distress and anxiety potentially evoked by group settings (Arnevik & Helverschou, ; Drake, Hank, Edwards, Ensum & Bateman, ; Rengit et al ., ). A series of studies by Kronenberg and colleagues (Kronenberg, Goossens, van Busschbach, van Achterberg & van den Brink, ; Kronenberg, Goossens, van Etten, van Achterberg & van den Brink, ; Kronenberg, Verkerk‐Tamminga, Goossens, van den Brink & van Achterberg, ) revealed that patients with SUD and co‐existing ASD had different needs regarding the quantity and quality of care in comparison to individuals with SUD, and SUD and comorbid ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Annand [4], Weiss [7], and the US department of health and human services, office on disability [8], suggest that the prevalence of those who have ID/DD as well as addiction ranges between 2 and 20%. A meta-analysis of eighteen papers published in Norway about autism spectrum disorder and substance use disorder resulted in twelve studies reporting on the prevalence of these co-occurring disorders ranging between 1-35% depending on the clinical samples [9]. Studies in Belgium, Denmark, and the Netherlands concluded that prevalence was frequently underestimated because individuals with mild intellectual disabilities were most often seen only by a single service provider.…”
Section: Introductionmentioning
confidence: 99%
“…This results in underestimating treatment and service needs [10,11]. A Swedish study found an increased risk for those with autism spectrum disorder, a pervasive developmental disability, to develop substance use-related problems, particularly those with co-morbid attention deficit hyperactivity disorder [9].…”
Section: Introductionmentioning
confidence: 99%